Implementation of Kupingan Method in Javanese Karawitan Music Training for Foreigners - Widodo, Widodo; Susetyo, Bagus; Walton, Susan; Appleton, William (Harmonia: Journal of Arts Research and Education, 2021)
The present work explores the implementation of kupingan method in the karawitan music training process to foreign participants with written tradition background. Moreover, it aims to identify, analyze, and elaborate the strength and weaknesses of kupingan method in transfer knowledge of gamelan skills. The present study employed a descriptive-qualitative method and class-action research design. The research objects involved the training of Javanese karawitan music to Tlaga Madu group from the University of Michigan in 2019. The data were obtained through observation of participation, interview, and document study. The data were further validated by triangulation technique and analyzed by steps as follows: identification, classification, verification, reduction, and explanation. The results indicate that kupingan method is applicable in the karawitan music training for foreigners, yet, to a very limited extent. By implementing the method, the training participants can master simple gending (colotomic structure) instrumental of learning materials, such as basic technique and patterns of instruments in the small-format gending lancaran form. On the other hand, the materials of complex gending with larger formats than lancaran are more effective to be disseminated by karawitan notation that is written in detail and elaborated with a demonstration of the song play.Â